Augmented rotations in virtual reality for users with a reduced range of head movement. (May 2019) - Norouzi, Nahal; Bölling, Luke; Bruder, Gerd; Welch, Greg
Introduction: A large body of research in the field of virtual reality is focused on making user interfaces more natural and intuitive by leveraging natural body movements to explore a virtual environment. For example, head-tracked user interfaces allow users to naturally look around a virtual space by moving their head. However, such approaches may not be appropriate for users with temporary or permanent limitations of their head movement. Methods: In this paper, we present techniques that allow these users to get virtual benefits from a reduced range of physical movements. Specifically, we describe two techniques that augment virtual rotations relative to physical movement thresholds. Results: We describe how each of the two techniques can be implemented with either a head tracker or an eye tracker, e.g. in cases when no physical head rotations are possible. Conclusions: We discuss their differences and limitations and we provide guidelines for the practical use of such augmented user interfaces.